Correction to: Consensus guideline for the diagnosis and treatment of tetrahydrobiopterin (BH4) deficiencies - Opladen, Thomas; López-Laso, Eduardo; Cortès-Saladelafont, Elisenda; Pearson, Toni S.; Sivri, H. Serap; Yildiz, Yilmaz; Assmann, Birgit; Kurian, Manju A.; Leuzzi, Vincenzo; Heales, Simon; Pope, Simon; Porta, Francesco; et al. (Orphanet journal of rare diseases, 2020)
An amendment to this paper has been published and can be accessed via the original article.